2020
DOI: 10.1136/vr.105567
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of dipotassium ethylenediaminetetraacetic acid but not lithium heparin affects total protein determination in equine synovial fluid

Abstract: BackgroundRefractometric determination of total protein (TP) in synovial fluid (SF) is commonly used for diagnosis and monitoring of synovial sepsis in horses. Previous studies have shown that elevated concentrations of certain anticoagulants may overestimate refractometric determination of TP concentration.ObjectivesThe aim of the study was to evaluate the effect of different concentrations of dipotassium EDTA (K2EDTA) and lithium heparin (LH) on TP determination by using a hand-held refractometer in equine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…This suggests that either heparin or EDTA salts may be used for anticoagulation to determine accurate TP concentrations. Rihuete et al 7 found, similar to our study, that the TP concentrations in equine SF were similar across the EDTA, heparin, and control groups, provided that the EDTA was used within the recommended concentrations. They showed that TP concentrations are only overestimated when EDTA is used in excess (more than four times the recommended 23 concentration of 1.2-2.0 mg/mL).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This suggests that either heparin or EDTA salts may be used for anticoagulation to determine accurate TP concentrations. Rihuete et al 7 found, similar to our study, that the TP concentrations in equine SF were similar across the EDTA, heparin, and control groups, provided that the EDTA was used within the recommended concentrations. They showed that TP concentrations are only overestimated when EDTA is used in excess (more than four times the recommended 23 concentration of 1.2-2.0 mg/mL).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Elevation of equine SF total protein (TP) to levels above 2 and 4 g/dL are likely compatible with inflammation and infection, respectively, while pH levels below 6.9 suggest the presence of joint infections. [6][7][8] Sample processing methods, storage times, and conditions affect the outcome of clinicopathologic and biochemical analyses. The American Society for Veterinary Clinical Pathology (ASVCP) Quality Assurance Guideline 9 emphasizes that the sample preparation method is an important source of pre-analytical errors, which not only encumbers reproducibility but also elevates the coefficient of variation of final results in metabolomic investigations.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations